AUTOIMMUNE HAEMOLYTIC ANEMIA IN 40 Y FEMALE: A CASE REPORT - PORWAL, VIPIN; DAMA, AASHISH; JAIN, PULKIT; SALVE, CHANDRA KANT (International Journal of Current Pharmaceutical Research, 2025)
The uncommon disorder referred to as autoimmune hemolyticanemia (AIHA) occurs when the immune system mistakenly attacks red blood cells, leading to the production of autoantibodies by the patient's body that destroy erythrocytes. A 40 y old female presented with complaint of shortness of breath aggravated on exertion, chest pain, palpitation over chest for 15 d. At the time of admission, her Hb was 5.5 g/dl, She is a case of autoimmune hemolyticanemia, ANA immunoblot shows Ro 60 was positive.